A Controlled Study on Personality Traits of Adults with and without Epilepsy - Sajida Agha, Muhammad Anwar Khan, Syed Waqas Hussain Shah (Pakistan Journal of Psychology, 2017)
The present study aimed to explore the personality traits in patients with epilepsy. In addition, the association of personality traits with different types of seizures in patients with epilepsy was also investigated. This case-controlled study comprised of 50 patients with epilepsy and a control group of 50 controls from general population who attended outpatient clinics of a community center in Saudi Arabia. The mean age calculated was 32.2 years (±SD=6.6, 6.3 respectively) for both groups. State-Trait Anxiety Inventory (STAI; Spielberger, Gorsuch, Lushene, Vagg, & Jacobs, 1983) and Personality Research Form (PRF; Jakson, 1984) were used. The t-test and One Way Analysis of Variance were employed to examine the differences. Patients with epilepsy scored higher on personality traits of trait anxiety and aggression whereas scored lower on achievement than the control group. Further, significant differences were observed between epileptic patients with different types of seizures on personality traits of trait anxiety and dominance only. The patients with generalized tonic-clonic scored high on trait anxiety whereas patients with absence seizures scored high on trait of dominance. The implications and avenues for future research are discussed.